Mythocritical analysis of Medea en Camariñas of Andrés Pociña: tradition and subversion of the classical myth - García Amorós, Maila (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
This paper analyses, from the point of view of intertextuality, Andrés Pociña’s dramatic monologue Medea en Camariñas. We assume as hypotexts three works of classical antiquity: Medea by Euripides, Medea by Seneca and Argonautics by Apollonius of Rhodes, since the author alludes to them explicitly, either in the opening lines or throughout the monologue. Moving into the field of mythocriticism, we analyse each of the mythemes present in Pociña’s work in relation to the hypotext, the way in which they appear and the approach that Pociña has sought to confer on his work through them.